1993
DOI: 10.1123/ijsn.3.4.356
|View full text |Cite
|
Sign up to set email alerts
|

Exercise, Oxidative Stress, and Antioxidants: A Review

Abstract: Elemental and gaseous oxygen presents a conundrum in that it is simultaneously essential for and potentially destructive to human life. Traditionally the ability to consume large volumes of oxygen has been assumed to be totally beneficial to the organism. In the past 10 years it has become clear that oxygen radicals are generated even during normal resting metabolism Nevertheless, such radicals are usually of no appreciable threat since a wide array of protective biochemical systems exist. However, under certa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0
5

Year Published

1995
1995
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(49 citation statements)
references
References 95 publications
(81 reference statements)
1
43
0
5
Order By: Relevance
“…Skeletal muscle, liver, heart, and brain, tissues with high oxygen consumption, have high antioxidant activities (19). In liver, the most oxidized protein is CAIII (6).…”
Section: Introductionmentioning
confidence: 99%
“…Skeletal muscle, liver, heart, and brain, tissues with high oxygen consumption, have high antioxidant activities (19). In liver, the most oxidized protein is CAIII (6).…”
Section: Introductionmentioning
confidence: 99%
“…There is some evidence that physically active people might lose, for instance, minerals and trace elements by heavy sweating (50) and in urine and feces (51). Exercise is likely associated with increased free radical uroduction (38). which could lead to an increased need for antioxidant vitamins > ,, and trace elements.…”
mentioning
confidence: 99%
“…The fact that aerobic training reduces oxidative stress is not surprising: the training protocol used in the present study (Figure 1) was indeed demonstrated to increase aerobic capacity and to counteract protein and lipid oxidative modifications in skeletal muscles of heart failure-bearing animals [34]. In addition, many investigators have reported that exercise training boosts antioxidant defenses [33,34,[72][73][74] while decreasing lipid peroxidation [29] and oxidative modifications to proteins and RNA [55]. groups of mice (Table 1) and allowed to determine differences caused by adaptation of muscle to lack of CASQ1 (control CASQ1-null versus WT) and to training (control versus trained CASQ1-null).…”
Section: Protection From Oxidative Stress and Damagementioning
confidence: 82%